Mechanistic insights into the Nongenomic regulation of Phospholipid synthesizing enzymes - Cardozo Gizzi, Andres Mauricio (2013)
Lipid synthesis is a complex process regulated at multiple levels. Here, we will discuss nongenomic regulatory mechanisms, particularly the activation and/or recruitment of key enzymes to membranes. The phospholipid synthesis enzymes Lipin and CTP:phosphocholine cytidylyltransferase are taken as examples of these mechanisms that are mediated by posttranslational modifications or by an intrinsic property of the enzyme that senses lipid composition. In addition, special emphasis will be put on another relevant non genomic lipid synthesis regulation mechanism that is dependent on c-Fos, a protein that has deserved less attention so far. This latter regulatory mechanism is emerging as an important determinant for processes that require high rates of lipid synthesis such as those of growth and proliferation.